Examination of military personnel’s changed psychological states during long-term deployment in a war zone - Kokun, Oleg; Pischko, Iryna; Lozinska, Natalia (Anales de Psicología / Annals of Psychology, 2022)
Examining military personnel’s psychological states is an effective way to prevent negative mental health consequences during their deployment in a war zone. The present study identifies changes in the psychological states of military personnel (n = 192) during a 6-month deployment in a war zone in eastern Ukraine. The results confirmed both of our proposed hypotheses. First, with regard to time limits on military personnel’s deployment on the front lines in eastern Ukraine on the basis of examined psychological states, the estimated recommended deployment duration was three months. Second, we found significant differences in the dynamics of the psychological states of service members with versus without previous deployment experience. The results also substantiate that military personnel’s psychological states should be monitored during deployment in order to prevent negative mental health consequences and to ensure that military units successfully accomplish their tasks.